Network analysis and subsequent culturing reveal keystone taxa involved in microbial litter decomposition dynamics - Zheng, Haiping; Yang, Tianjie; Bao, Yanzhuo; He, Panpan; Yang, Keming; Mei, Xinlan; Wei, Zhong; Xu, Yangchun; Shen, Qirong; Banerjee, Samiran (Soil biology & biochemistry, 2021)
Plant litter decomposition in the soil is governed by microorganisms such as bacteria and fungi that colonize lignocellulose residues during the decomposition process, and thus, the interplay of bacterial and fungal communities can yield insight into the lignocellulose decomposition dynamics. Previous studies have mainly investigated litter decomposing communities in microcosms or ex-situ conditions or at a single soil ecosystem. Here we conducted a 12 week-long litter decomposition experiment to explore how the temporal dynamics of soil enzyme activities and microbial communities are linked to litter decomposition under three different land use sites (forestland, farmland, and abandoned farmland) in Nanjing, China. We found that litter decomposition in the forestland was the highest among the three land use sites. Then, using a multifactorial approach, we showed that this higher decomposition rate in forest soils is determined by microbial communities with higher ligninolytic enzyme activities, higher diversity, and a less complex but more specialized network. Chryseobacterium in bacteria, and Fusarium, Aspergillus and Penicillium in fungi were the keystone taxa in networks across three land use types. We conducted subsequent culturing that further confirmed the strong decomposition ability and enzyme activities of these taxa, indicating their importance for microbial litter decomposition. As such, this is one of the first studies to validate the role of keystone taxa for litter decomposition, and it demonstrates that co-occurrence network scores can be used for statistical identification of putative keystone taxa for further screening and linking to microbiome functioning. Overall, we show that land use alters the composition and network structure of soil microbiota that determine the litter decomposition. Our study also reveals that specialized keystone taxa are involved in the decomposition dynamics, and highlights an opportunity of harnessing such taxa for manipulating lignocellulose decomposition in soil ecosystems. •Forestland had the highest litter decomposition and lignocellulolytic enzyme activities.•Forestland had greater microbial diversity and a specialized microbial network.•Culturing supported the role of keystone taxa in litter decomposition.